2013
DOI: 10.1179/1476830513y.0000000059
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fermented red ginseng on depression is mediated by lipids

Abstract: Based on the analysis used in this model, the effect of FRG consumption on CD occurred via the energy factor, which is mainly attributable to cholesterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…Clinical studies on 35 female outpatients aging from 18 to 65 years who were remitted from major depression with residual symptoms and given Korean Red Ginseng at a dose of 3 g/day reported significant decrease in depressive symptoms on the Depression Residual Symptom Scale (DRSS) and Montgomery-Åsberg Depression Rating over an 8-week period (Jeong et al, 2014 ). Another study of possible casual relation between hormones, energy sources, and minerals indicated that depression was related to serum lipids including cholesterol, and that fermented red ginseng had beneficial effects on depression by modulating this relation (Lee and Ji, 2014 ).…”
Section: Protective Effects Of Ginseng On Neurological Disordersmentioning
confidence: 99%
“…Clinical studies on 35 female outpatients aging from 18 to 65 years who were remitted from major depression with residual symptoms and given Korean Red Ginseng at a dose of 3 g/day reported significant decrease in depressive symptoms on the Depression Residual Symptom Scale (DRSS) and Montgomery-Åsberg Depression Rating over an 8-week period (Jeong et al, 2014 ). Another study of possible casual relation between hormones, energy sources, and minerals indicated that depression was related to serum lipids including cholesterol, and that fermented red ginseng had beneficial effects on depression by modulating this relation (Lee and Ji, 2014 ).…”
Section: Protective Effects Of Ginseng On Neurological Disordersmentioning
confidence: 99%
“…Korean red ginseng powder also reduced urinary BPA and MDA levels in young females and reduced the severity of gynecological complaints [ 9 ]. Fermented red ginseng improved cognitive depression in postmenopausal females [ 51 ]. Panax ginseng extract (G115) reduced noise-induced temporary threshold shifts in textile workers [ 44 ], but had no effect on pain and fatigue in patients with fibromyalgia [ 45 ] .…”
Section: Resultsmentioning
confidence: 99%
“…In parallel with this, there have been several clinical trials on depression. Lee and Ji [53] showed that fermented red P. ginseng had beneficial effects on depression by altering lipids. In addition, Jeong et al.…”
Section: Disease Analysismentioning
confidence: 99%